Phenotypic and Epigenetic Adaptations of Cord Blood CD4+ T Cells to Maternal Obesity - Sureshchandra, Suhas; Mendoza, Norma; Jankeel, Allen; Wilson, Randall M.; Marshall, Nicole E.; Messaoudi, Ilhem (Frontiers in Immunology, 2021)
ABSTRACT Pregravid obesity has been shown to disrupt the development of the offspring’s immune system and increase susceptibility to infection. While the mechanisms underlying the impact of maternal obesity on fetal myeloid cells are emerging, the consequences for T cells remain poorly defined. In this study, we collected umbilical cord blood samples from infants born to lean mothers and mothers with obesity and profiled CD4 T cells using flow cytometry and single cell RNA sequencing at resting and following ex vivo polyclonal stimulation. We report that maternal obesity is associated with higher frequencies of memory CD4 T cells suggestive of in vivo activation. Moreover, single cell RNA sequencing revealed expansion of an activated subset of memory T cells with maternal obesity. However, ex vivo stimulation of purified CD4 T cells resulted in poor cytokine responses, suggesting functional defects. These phenotypic and functional aberrations correlated with methylation and chromatin accessibility changes in loci associated with lymphocyte activation and T cell receptor signaling, suggesting a possible link between maternal obesogenic environment and fetal immune reprogramming. These observations offer a potential explanation for the increased susceptibility to microbial infection in babies born to mothers with obesity.